Research on human resource management of international enterprises based on competency model under cross-cultural background - Li, Qin; Mohamed, Rosmah (Mattingley Publishing, 2020)
Human resources are the strategic resources of enterprises in the 21st century, the decisive factor of enterprise development and the core strength of management. At present, there are some cross-cultural issues in the human resource management of multinational companies, such as communication issues and cultural gaps. When the company develops multinational operations, the company may be affected by diverse cultures from the same country, including another value, concept, and action affected by the culture. Human resource management theory has far-reaching cultural significance, and cultural differences use human actions to bring significant and irreversible changes to the efficiency of the team. Competence refers to all the personal traits that can be objectively measured by people with outstanding performance in the exclusive career, team and cultural environment. This article introduces the cross-cultural human resource management in multinational corporations based on the competency model, so as to more fully utilize and manage human resources in various cultural atmospheres.